Efektivitas Kampanye Clean & Clear “Bangga dengan Warna Kulitmu” dalam Meningkatkan Kepercayaan Diri Remaja Putri - Nainggolan, Herti Yuliana; Erdiansyah, Rezi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Representation of women's beauty with white skin has become the minimum standard that must be possessed by every woman in Indonesia, especially young women. However, unfortunately there are still many women in Indonesia who still agree and admit that beauty must be white. Clean & Clear then responded to the news representation by creating a campaign with the aim of changing the mindset of young women in Indonesia through the concept of self-confidence. The campaign carries the concept of